Intrinsically Chiral Twist‐Bend Nematogens: Interplay of Molecular and Structural Chirality in the NTB Phase. Issue 6 (15th December 2022) - Walker, Rebecca; Pociecha, Damian; Salamonczyk, Miroslaw; Storey, John M. D.; Gorecka, Ewa; Imrie, Corrie T.
Abstract: Non‐symmetric lactate‐based chiral liquid crystal dimers containing an odd‐membered spacer are shown to exhibit a chiral twist‐bend nematic phase which is stable on cooling to room temperature. A comparison of racemic and optically pure materials reveals that the pitch length in the N*TB phase is not influenced by molecular chirality, whereas the nematic‐twist‐bend nematic transition temperature is increased. Abstract : Relationships between intrinsic and structural chirality in dimeric liquid crystals are explored using new lactate‐based chiral compounds exhibiting the rarely‐observed chiral N*TB phase. Comparisons of enantiomeric and racemic nonsymmetric dimer pairs show that optically pure materials have higher values of TN * TB ${{_{{*}{_{{\rm TB}}}}}}$ N* than their racemic analogues, in perfect accordance with the theory that chiral doping increases the stability of the NTB phase relative to the N phase.